Method for effective dead time measurement in counting systems - Vinagre, F. L. R. (2001)
The counting losses introduced by the dead time of a counting system are a limiting factor in counting measurements. The purpose of this work is to report an efficient method for the measurement of the effective dead time of a counting system and to characterize its dead time behavior, providing a way to investigate each experimental situation. The method, which we designate as Delayed and Mixed Pulses method, is based on the artificial piling-up of detector pulses with electronic pulses delayed by a specific time interval. It is applicable to the measurement of the effective dead time of a counting system, including both pile-up effects and the dead time characteristics of the elements of the counting chain. With counting systems relying on gaseous radiation detectors, we achieved a standard uncertainty of about 5-10% in the dead times measured.